Association between imaging and clinical findings in mandibular third molar surgeries (Revista da Faculdade de Odontologia - UPF, 2018)
Objective: it is important to evaluate the position andestablish the third molar relationship with the mandibularcanal to minimize the risk of nerve injury and assistin planning the extraction of this tooth. The panoramicradiograph is the standard diagnostic tool for this purpose.However, if it indicates a close relationship betweenthe third molar and the mandibular canal, furtherinvestigation using cone beam computed tomography(CBCT) may be recommended to check the three-dimensionalrelationship between the tooth and the mandibularcanal. Thus, this study aimed to correlate the clinicalfindings (observed in third molar surgeries) to imagingfindings (observed in panoramic radiographs andCBCT). Subjects and method: after the extraction of 20mandibular third molars, the panoramic radiograph andthe cone beam computed tomography were analyzed.Then, the surgical findings were correlated to the imagefindings. Results: It was observed that the radiographicfinding type 2 (darkening of roots) observed in the panoramicradiograph presented a greater relation to theabsence of cortical bone between the mandibular canaland the third molar (CBCT finding), with statistical significance(p